Detekce volných lehkých retezců ("free light chains")--nová metoda diagnostiky hematologickyćh onemocneí - Mecl, J; Benáková, H; Nohejlová, A; Straub, J; Zima, T; Spicka, I (Casopis lekaru ceskych, 2007)
BACKGROUND: To diagnose monoclonal gamopathy, one of the most frequent haematological diseases, we use immunochemical assays, which are based on the detection of paraprotein in serum and/or urine. METHODS AND RESULTS: The most common laboratory assays we use are SPE (serum protein electrophoresis) and IFE (immunofixation electrophoresis). New method represents the detection of free light chain (FLC) in serum. In our study we compared those three methods (SPE, IFE and FLC) from the point of sensitivity of paraprotein detection. For FLC detection was used Freelite system analyzer (Immunotech Beckman Coulter). We examined 51 patients with diagnosis of multiple myeloma, nonHodgkin's lymphoma, primary amyloidosis and monoclonal gammopathy of undetermined significance. CONCLUSIONS: Detection of FLC is a valuable method which sometimes could specify diagnosis of MG and make the treatment more accurate.
Keywords: senioři; Paraproteinemias; senioři nad 80 let; Immunoglobulin Light Chains; elektroforéza sérových bílkovin; Middle Aged; mužské pohlaví; lehké řetězce imunoglobulinů; Adult; Blood Protein Electrophoresis; paraproteinemie; Aged, 80 and over; imunoelektroforéza; ženské pohlaví; Humans; biologické markery; lidé středního věku; dospělí; Biomarkers; Immunoelectrophoresis; Female; Aged; lidé; Male